Thomas O. Paine papers - Paine, Thomas O., 1921-1992.
Correspondence, memoranda, reports, minutes of meetings, appointment books, family and genealogical papers, and printed matter chiefly relating to Paine's engineering career with General Electric Company and Northrop Corporation and as deputy and acting administrator at NASA, where he directed seven Apollo missions, including the first to the moon. Also includes a journal (1945) kept by Paine while serving in the U.S. Navy describing the demilitarization of Japanese submarines during the early days of the Allied occupation of Japan; and material relating to Paine's service as chairman of the National Commission on Space and as a member of the Advisory Committee on the Future of the United States Space Program and Engineers Joint Council. Paine's interest in interplanetary exploration and colonization is documented by papers relating to the Case for Mars conferences and drafts of books and screenplays by others on outer space exploration. Correspondents include Buzz Aldrin, Ray Bradbury, John Glenn, J. Herbert Holloman, Thomas V. Jones, and Robert C. Seamans.
Microfilm edition available of a petition (6 Feb. 1969) concerning the use of religious references by the Apollo astronauts
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Engineer, corporate executive, and National Aeronautics and Space Administration official. Full name: Thomas Otten Paine; died 1992.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aldrin, Buzz -- Correspondence; Bradbury, Ray, -- 1920-2012 -- Correspondence; Glenn, John, -- 1921- -- Correspondence; Hollomon, J. Herbert -- Correspondence; Jones, Thomas V., -- 1920- -- Correspondence; Seamans, Robert C. -- Correspondence; Engineers Joint Council; General Electric Company; Northrop Corporation; Project Apollo (U.S.); United States. -- Advisory Committee on the Future of the U.S. Space Program; United States. -- National Aeronautics and Space Administration; United States. -- National Commission on Space; United States. -- Navy -- Foreign service -- Japan; Planets -- Exploration; Space colonies; Space flight to the moon; Submarines (Ships) -- Japan; Japan -- History -- Allied occupation, 1945-1952.; Mars (Planet); Outer space -- Exploration; Engineers